Perancangan Video Animasi 2 Dimensi Cerita Rakyat Malin Kundang dengan Aplikasi Toon Boom Harmony - Nico Putra Tanuwijaya; Tony Wibowo (Journal of Information System and Technology (JOINT), 2020)
There are not many instructional media in schools that focusses on Indonesian folklore, this project aims to design a 2D animation video about Malin Kundang with the MDLC (Multimedia Development Life Cycle) method and uses the Toon Boom application, which then can be used by teachers as an instructional media for students at school. The final result of this project is a 5 minutes and 20 seconds video, and after interviewing a few teachers, the video’s feedback is that it is effective to be used as an instructional media.